The Mystery of Sol - Kubuitsile, Lauri; Illustrated by Xavier Bonet (UK Cambridge, 2017)
Endorsed for reading by Cambridge Assessment International Education, Cambridge Reading Adventures is our international primary reading scheme.
Including color illustrations
Keywords: Readers (Elementary) -- Children's plays, American